LApIS: developing research applied to health care area - Nunes, Fátima L S; Bíscaro, Helton H; Delamaro, Márcio E; Tori, Romero; Nakamura, Ricardo (Journal on Interactive Systems, 2011)
The Laboratory of Computer Applications for Health Care is a Brazilian lab researching in the virtual reality, Content-based image retrieval, and image processing areas, mainly developing applications to the health care area, although many of the techniques and tools extrapolate this application scope. . In this paper we present a brief history of the laboratory, its mission as well as current projects and collaborations. All the projects developed at LApIS have some relevant aspects for researches in the graphics area, which can become new opportunities for student’s integration and new collaborations.